Trajectories of health-related quality of life by socio-economic status in a nationally representative Canadian cohort. Issue 7 (24th March 2011) - Ross, Nancy A; Garner, Rochelle; Bernier, Julie; Feeny, David H; Kaplan, Mark S; McFarland, Bentson; Orpana, Heather M; Oderkirk, Jillian
Abstract : Background: Mortality and morbidity have been shown to follow a 'social gradient' in Canada and many other countries around the world. Comparatively little, however, is known about whether ageing amplifies, diminishes or sustains socio-economic inequalities in health. Methods: Growth curve analysis of seven cycles of the Canadian National Population Health Survey (n=13 682) for adults aged 20 and older at baseline (1994/95). The outcome of interest is the Health Utilities Index Mark 3, a measure of health-related quality of life (HRQL). Models include the deceased so as not to present overly optimistic HRQL values. Socio-economic position is measured separately by household-size-adjusted income and highest level of education attained. Results: HRQL is consistently highest for the most affluent and the most highly educated men and women, and is lower, in turn, for middle and lower income and education groups. HRQL declines with age for both men and women. The rate of the decline in HRQL, however, was related neither to income nor to education for men, suggesting stability in the social gradient in HRQL over time for men. There was a sharper decline in HRQL for upper-middle and highest-income groups for women than for the poorest women. Conclusion: HRQL is graded by both income and education in Canadian men and women. The grading of HRQL by social position appears to be 'set' in early adulthood and is stable through mid- and later life.